Conformable Integral Inequalities of the Hermite-Hadamard Type in terms of GG- and GA-Convexities. (10th January 2019) - Khurshid, Yousaf; Adil Khan, Muhammad; Chu, Yu-Ming
Abstract : In the article, we present several conformable fractional integrals' versions of the Hermite-Hadamard type inequalities for GG- and GA-convex functions and provide their applications in special bivariate means.